ICT TOOLS AND INNOVATIVE APPROACH IN PEDAGOGICAL PROCESSES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
The article also provides general information about pedagogical processes and opinions on the types of ICT tools. However, innovative approaches to pedagogical tools have also been analyzed using examples.